2019
DOI: 10.1088/1755-1315/309/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Arabica Java Coffee Beans Based on Their Origin using NIR Spectroscopy

Abstract: The NIR spectroscopy for characterization and classification of intact Java arabica coffee beans based on their origin is proposed. Commonly, NIR spectroscopy is used to determine composition of agricultural products including coffee. Three kinds of Java arabica coffee beans namely Arabica Java Preanger, Arabica Bondowoso and Arabica Malang were used in this research. Three hundred samples, each consisted of 100 g coffee beans were prepared. The coffee beans of 100 g were placed in petri dish and the light ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…A discriminant analysis (DA) with an accuracy rate of 95-100% was used to classify three arabica green coffee beans from Java Island, Indonesia (Java Preanger, Bondowoso, and Malang). Long wavelength NIR spectra were measured for intact green coffee bean samples in the range of 1000-2500 nm [62]. Bona et al [63] reported the application of Fourier transform near-infrared (FT-NIR) spectroscopy combined with the support vector machine (SVM) classification method to differentiate several arabica green coffee beans from different regions in Brazil.…”
Section: Classification Model Development Results Using Pls-da Lda An...mentioning
confidence: 99%
“…A discriminant analysis (DA) with an accuracy rate of 95-100% was used to classify three arabica green coffee beans from Java Island, Indonesia (Java Preanger, Bondowoso, and Malang). Long wavelength NIR spectra were measured for intact green coffee bean samples in the range of 1000-2500 nm [62]. Bona et al [63] reported the application of Fourier transform near-infrared (FT-NIR) spectroscopy combined with the support vector machine (SVM) classification method to differentiate several arabica green coffee beans from different regions in Brazil.…”
Section: Classification Model Development Results Using Pls-da Lda An...mentioning
confidence: 99%
“…It provides several advantages ; fast and easy to do, it does not require chemicals, and able to perform internal quality tests on agricultural products non-destructively. This method has also widely studied in agriculture field to determine physicochemical content of agricultural products such as catechin in gambir [3], fat and free fatty acid in jatropha [4], trigonelline, chlorogenic acid, caffeine content of coffees [5] [6], and classification of coffee origin [7]. Research on the estimation of vanillin and moisture content in Thailand' vanilla using NIRS has been carried out [8].…”
Section: Introductionmentioning
confidence: 99%
“…The application of NIR method in coffee products has been conducted and the result exhibited a high correlation between NIR data and the chemical data while building NIR model determination for several chemical concentration such as caffeine[2,4-5], trigonelline [6], lipid [7], chlorogenic acid [6], protein, carbohydrate [7] and water [8] content using various data processing method. Beside that, study about coffee characterization based on NIR data according to its growing location also had done [9][10].…”
Section: Introductionmentioning
confidence: 99%